The nexus between climate change, mobility and social tensions in Mozambique - Ndlovu, Sindiso; Sax, Niklas; Maviza, Gracsious; Caroli, Giulia; Makanda, Joseph (2024)
Mozambique faces substantial challenges due to its susceptibility to climate variability and change, exacerbated by its coastal location. This vulnerability contributes to a complex interplay between climate-induced impacts, mobility patterns, and escalating social tensions. This paper explores the possible dynamics of interaction between climate change and displacement and the resultant adverse impacts on social tensions and stability. It draws on an extensive literature review and can be used as a starting point for the design and planning of effective policy and operational responses across the Humanitarian-Development-Peace (HDP) nexus.